1997
DOI: 10.1021/jp961912j
|View full text |Cite
|
Sign up to set email alerts
|

Electron Momentum Spectroscopy Study of Lone Pair Orbitals of Thiols and Dimethyl Sulfide

Abstract: Experimental momentum profiles of the lone pair orbitals of several thiols and dimethyl sulfide have been measured and compared with theoretical momentum profiles. All the observed profiles exhibit p-type character, confirming that the orbitals have been characterized as sulfur nonbonding orbitals. However, small shifts in the profiles are found, depending on substituents. The results are discussed in relation to the geometries of the molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As indirectly known from the electron momentum spectroscopic study, the HOMO of the neutral ground-state of ethanethiol is mainly localized on sulfur, while it has a nodal plane bisecting the C−S bond (Figure ). Furthermore, it is found that, from the CASSCF(3,4) calculation with a 6-31G** basis set, the singly occupied molecular orbital (SOMO) of the ethanethiol cation is not only localized on sulfur, but it is also fully occupied, meaning that the multireference nature of the orbital may not be significant in this case.…”
Section: Resultsmentioning
confidence: 97%
“…As indirectly known from the electron momentum spectroscopic study, the HOMO of the neutral ground-state of ethanethiol is mainly localized on sulfur, while it has a nodal plane bisecting the C−S bond (Figure ). Furthermore, it is found that, from the CASSCF(3,4) calculation with a 6-31G** basis set, the singly occupied molecular orbital (SOMO) of the ethanethiol cation is not only localized on sulfur, but it is also fully occupied, meaning that the multireference nature of the orbital may not be significant in this case.…”
Section: Resultsmentioning
confidence: 97%
“…Very recently, we have developed an energy-and angle-dispersive EMS spectrometer [11]. It has taken a significant advantage of multichannel detection, realizing experiments at much higher precision than achieved with our previous apparatus [12].…”
Section: Introductionmentioning
confidence: 99%
“…The valence orbitals of (CH 3 ) 2 S were also investigated by electron momentum spectroscopy (EMS). , EMS is a unique technique for exploring electronic structures of atoms and molecules. It is based on the fast electron impact binary (e, 2e) reaction near the Bethe ridge condition. Within a series of approximations including binary encounter, weak coupling, plane wave impulse, as well as target Hartree–Fock (HF) or target Kohn–Sham (KS) approximations, , the measured (e, 2e) triple differential cross section (TDCS) is proportional to the spherically averaged modulus square of the electron wave function of the ionized orbital in the momentum space or the electron momentum profile (EMP).…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the fast electron impact binary (e, 2e) reaction near the Bethe ridge condition. Within a series of approximations including binary encounter, weak coupling, plane wave impulse, as well as target Hartree–Fock (HF) or target Kohn–Sham (KS) approximations, , the measured (e, 2e) triple differential cross section (TDCS) is proportional to the spherically averaged modulus square of the electron wave function of the ionized orbital in the momentum space or the electron momentum profile (EMP). Takahashi et al obtained the EMP of 3b 1 , the highest occupied molecular orbital (HOMO) of (CH 3 ) 2 S, with limited statistics. The shift of the EMP to higher momentum was observed due to the delocalization of the sulfur 3p lone pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation